318 INTRA-ABDOMINAL FAT PREDICTS FUTURE DEVELOPMENT OF THE METABOLIC SYNDROME IN NON-DIABETIC JAPANESE-AMERICANS. (1st January 2005) - Tong, J.; McNeely, M. J.; Hull, R. L.; Carr, D. B.; Utzschneider, K. M.; Shofer, J. B.; Boyko, E. J.; Leonetti, D. L.; Kahn, S. E.; Fujimoto, W. Y.
Abstract : Visceral adiposity is an important risk factor for both coronary heart disease and type 2 diabetes. Recent cross-sectional studies demonstrated that intra-abdominal fat (IAF) was a major determinant of the metabolic syndrome. We hypothesized that higher intra-abdominal fat independently predicts the development of the metabolic syndrome and each of the individual criteria in Japanese-Americans. Research Design and Methods: 495 Japanese-American men (n=250, mean age 51.8 years, mean BMI 25.0 kg/m2) and women (n=245, mean age 52.3 years, mean BMI 22.8 kg/m2) without diabetes or the metabolic syndrome at baseline were studied. At baseline and at 5-year and 10-year follow-up, IAF area by CT, fasting plasma glucose and insulin, blood pressure, triglycerides, HDL cholesterol and waist circumference were measured. Insulin resistance (IR) was estimated by the fasting insulin (FI) level. Linear regression was used to estimate the association between IAF, IR and the development of metabolic syndrome as defined by the National Cholesterol Education Program Adult Treatment Panel III at 5- and 10-year follow-up. Results: The 5-year incidence of the metabolic syndrome was 7.1% (7.0% in men and 7.2% in women), and the 10-year incidence was 9.1% (11.3% in men and 6.8% in women). IAF area at baseline was associated with metabolic syndrome incidence at 5 years (coefficient=0.022, p≤0.001) and at 10 years (coefficient=0.017, p≤0.001) after adjusting for age and gender. FI level at baseline was also significantly associated with metabolic syndrome incidence at 5 years (coefficient=0.073, p=0.001) and at 10 years (coefficient=0.074, p = 0.001), but this finding was not independent of IAF. Furthermore, baseline IAF was significantly associated with each individual criteria of the metabolic syndrome at both 5- and 10-year follow-up. Conclusions: IAF area at baseline independently predicts the development of the metabolic syndrome and each of its individual criterion in Japanese-Americans in both short (5 years) and long term (10 years) follow-up. IAF appears to have a stronger association with metabolic syndrome incidence than does insulin resistance.